The Relationship Between Women Entrepreneurial Competencies, Business Competitive Advantage And Firm Performance In Nigeria - ., Mohammed Kabir (2017)
This study examined the direct and indirect relationships between entrepreneurial competencies, cost leadership strategy and firm performance of women entrepreneurs in Nigeria. Evidence indicates that for women entrepreneurs in Nigeria to succeed in running their businesses effectively and efficiently, they need to equip themselves with necessary competencies and strategy. Linking relationship between these variables in running successful business venture, a research framework was proposed for empirical research. Hypotheses were formulated with the view of evaluating the relationship between entrepreneurial competencies, cost leadership strategy and firm performance.